Strategi Pengembangan UMKM Industri Tahu di Kecamatan Gunung Putri Kabupaten Bogor (Studi Kasus di CV. Wahyu Utama) - Awalia Syafitri; Kardiman Kardiman; Safira Fathin (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2023)
This study aims to identify the internal and external factors influencing the performance of the tofu MSME, CV. Wahyu Utama, in Bojongkulur. MSMEs in Indonesia compete with each other based on product quality. Therefore, to win, they must analyze appropriate business development strategies. The methods used in this study were SWOT analysis, IFE (Internal Factor Evaluation), and EFE (External Factor Evaluation). The data used were primary and secondary data, using descriptive quantitative analysis. The IFE calculation yielded a score of 3.08, indicating a strong strength and weakness factor. The EFE calculation yielded a score of 2.48, indicating a moderate opportunity and threat factor. The IE analysis results placed the company in quadrant IV, indicating that CV. Wahyu Utama's development strategy is growing and developing.